ANALISA PENGARUH WIND SHIELD DAN REAR BOX TERHADAP GAYA HAMBAT UDARA PADA SEPEDA MOTOR - Legowoh, Ragel Nasrulloh; Fahruddin,; Akbar, Ali (Universitas Negeri Surabaya, 2024)
One of the favorite vehicles in cities and villages is a motorbike because it is practical and economical. So most of them modify their motorbikes. Starting from adding accessories such as a wind shield and rear box. An aerodynamic vehicle body shape can have an effect on reducing fuel consumption and minimizing forces that hinder the vehicle's speed. This research aims to see the difference in air resistance between motorbikes that have been modified and those that have not been modified. The simulation used uses a numerical simulation method with CFD (Computational Flow Dynamics) software. The form of modification is the addition of a wind shield and rear box. The average speed travelled in the flow simulation is 60 km/hour. The equations used in this research are the drag coefficient, velocity, drag force and flow trajectory equations. The research results show that the Windshield and Rear Box have a very significant influence on drag force. The higher the speed given, the greater the resistance force received. The addition of accessories such as a wind shield and rear box affects the drag force on a motorbike, which is the greatest at 205.28N for a speed of 80 km/hour. The largest drag coefficient is also obtained when these two accessories are added, namely 0.0071 at a speed of 80 km/hour.